Molecular Imaging with PET/CT in Oncology - Pejman Farde esfehani; Babak Fallahi; davood Beigi; Armaghan Farde esfehani; Alireza Emami Ardakani; Mohammad Eftekhari; Mojtaba Ansari (Iranian South Medical Journal, 2012)
Background: Molecular imaging is a novel method to evaluate cellular function at molecular level without any cell disturbance. Among the molecular imaging modalities, positron emission tomography (PET), especially when fused with computed tomography (CT), has brought an additional dimension to management of patients with can. Methods: The method employed in this research was a systematic bibliographic review, in which only valid studies or the clinically detailed enough open-labeled studies using validated scales were used. Results: Molecular imaging by PET/CT provides valuable means to assess functional disorders along with anatomical abnormalities in malignant tumors. Increased metabolism induced by malignant cells results in increased uptake in PET images, localization of which is accurately done by using CT scan. This method has been particularly of value in chest lesions (including pulmonary nodules), colorectal cancer, head and neck tumors and lymphoma. The major role of PET/CT appears to be in the preoperative disease staging, response to treatment assessment, and post-treatment disease. PET-CT shows better results than conventional anatomical imaging alone and thereby can assist in better patient management. Disease prognosis and radiotherapy planning are evolving areas where this modality has demonstrated significant promise. Conclusion: Combination of PET and CT in a single system (PET/CT) to form fused anatomical and functional information has provided an imaging modality which could be used as the major tool in detection, staging and restating of tumors. It is also of great value for accurate preparation of radiotherapy treatment plans.